2020
DOI: 10.1101/2020.12.14.20248176
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide analysis in 756,646 individuals provides first genetic evidence that ACE2 expression influences COVID-19 risk and yields genetic risk scores predictive of severe disease

Abstract: The need to identify and effectively treat COVID-19 cases at highest risk for severe disease is critical. We identified seven common genetic variants (three novel) that modulate COVID-19 susceptibility and severity, implicating IFNAR2, CCHCR1, TCF19, SLC6A20 and the hyaluronan pathway as potential therapeutic targets. A high genetic burden was strongly associated with increased risk of hospitalization and severe disease among COVID-19 cases, especially among individuals with few known risk factors.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 75 publications
1
27
0
1
Order By: Relevance
“…Furthermore, we exploited this mechanistic insight and treated animals with rmsACE2 inhalation and observed a substantial protection of BALB/c and C57BL/6 mice from developing mCOVID-19 . A recently published genome-wide association study across more than 50 000 COVID-19 patients and more than 700 000 non-infected individuals revealed a rare variant that was associated with down-regulated ACE2 expression and reduced risk of COVID-19 (Horowitz et al , 2021), providing additional evidence for the importance of ACE2 for SARS-CoV-2 infection in humans. The principal effectiveness of recombinant human soluble (rhs) ACE2 towards SARS-CoV-2 was demonstrated earlier in organoids, as it slowed viral replication in this setting (Monteil et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we exploited this mechanistic insight and treated animals with rmsACE2 inhalation and observed a substantial protection of BALB/c and C57BL/6 mice from developing mCOVID-19 . A recently published genome-wide association study across more than 50 000 COVID-19 patients and more than 700 000 non-infected individuals revealed a rare variant that was associated with down-regulated ACE2 expression and reduced risk of COVID-19 (Horowitz et al , 2021), providing additional evidence for the importance of ACE2 for SARS-CoV-2 infection in humans. The principal effectiveness of recombinant human soluble (rhs) ACE2 towards SARS-CoV-2 was demonstrated earlier in organoids, as it slowed viral replication in this setting (Monteil et al , 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Horowitz et al showed that a high genetic burden from seven common genetic variants that modulate COVID-19 susceptibility and severity was strongly associated with increased risk of hospitalization and severe disease among COVID-19 cases, especially among individuals with few known risk factors. Using genetics to identify individuals at highest risk of adverse outcomes may therefore help prioritize individuals for immunization by (mRNA) vaccines or for treatment with monoclonal antibody treatments when they are still in short supply [27].…”
Section: Individual and Clinical Decision Makingmentioning
confidence: 99%
“…Factors contributing to disease severity include anthropometric factors (e.g., age, gender, BMI), comorbidities (e.g., hypertension, diabetes) and unhealthy habits (e.g., smoking) [3]. Host genetics studies in COVID-19 have reported genomic variations associated with disease severity in chromosomes 1 (1q22.1), 2 (2p21.1), 3 (3p21.1-3), 6 (6p21.1), 8 (8q24.13), 9 (9q34.1-2), 12 (12q24.1-2), 17 (17q21.3), 19 (19p13.1-3) and 21 (21q21-q22) as well as in specific loci that have been manually selected [4][5][6][7][8]. The COVID Host Genetics Initiative has set up one of the largest communities that are currently generating, sharing and analyzing data to learn the genetic determinants of COVID-19 susceptibility, severity and outcomes.…”
Section: Impact Of Human Genome On Covid-19mentioning
confidence: 99%